Decision Support System in Determining the Level of Customer Satisfaction in the SME Corner at the Department of Cooperatives, Small and Medium Enterprises, Deli Serdang Regency with the Analytical Hierarchy Process (AHP) Method - Laphita Sari Simanjuntak (International Journal of Basic and Applied Science, 2021)
In order to increase customer satisfaction at the SME Corner of Deli Serdang, a research was conducted on the level of customer satisfaction in the SME Corner of Deli Serdang. To find out the extent to which the SME Corner's ability to provide satisfaction through its products, services, finances, delivery and company conditions, information marketing research is needed from the results of the marketing research aimed at knowing the attitudes and behavior of customers towards what is most influential in making decisions to become SME Corner customers in Department of Cooperatives, Small and Medium Enterprises Deli Serdang Regency. This study starts from the stage of analyzing the current system obtained from direct interviews with related parties and observations. While the design method uses the Unified Modeling language (UML) to describe the system design. In this case, to calculate the level of customer satisfaction, the AHP (Analytical Hierarchy Process) method is used. By using a decision-making system, it can provide convenience for the Deli Serdang UKM Corner to determine customer satisfaction in improving the quality to determine the level of customer satisfaction which is applied using PHP programming and MySql database. The system was developed using a software engineering approach, including analysis, design and implementation. At the analysis stage, process analysis, input analysis, output analysis, weakness analysis of the current system and needs analysis are carried out.